Low dose dietary nitrate improves endothelial dysfunction and plaque stability in the ApoE-/- mouse fed a high fat diet - Bakker, J.; Bondonno, N.; Gaspari, T.; Kemp-Harper, B.; McCashney, A.; Hodgson, J.; Croft, K.; Ward, Natalie (Elsevier, 2016)
Background: Nitric oxide (NO) is an important vascular signalling molecule. NO is synthesised endogenously by endothelial nitric oxide synthase (eNOS). An alternate pathway is exogenous dietary nitrate, which can be converted to nitrite and then stored or further converted to NO and used immediately. Atherosclerosis is associated with endothelial dysfunction and subsequent lesion formation. This is thought to arise due to a reduction in the bioavailability and/or bioactivity of endogenous NO. Aim: To determine if dietary nitrate can protect against endothelial dysfunction and lesion formation in the ApoE-/- mouse fed a high fat diet (HFD). Methods and results: ApoE-/- fed a HFD were randomized to receive (i) high nitrate (10 mmol/kg/day, n=12), (ii) moderate nitrate (1 mmol/kg/day, n=8), (iii) low nitrate (0.1 mmol/kg/day, n=8), or (iv) sodium chloride supplemented drinking water (control, n=10) for 10 weeks. A group of C57BL6 mice (n=6) received regular water and served as a healthy reference group. At 10 weeks, ACh-induced vessel relaxation was significantly impaired in ApoE-/- mice versus C57BL6. Mice supplemented with low or moderate nitrate showed significant improvements in ACh-induced vessel relaxation compared to ApoE-/- mice given the high nitrate or sodium chloride. Plaque collagen expression was increased and lipid deposition reduced following supplementation with low or moderate nitrate compared to sodium chloride, reflecting increased plaque stability with nitrate supplementation. Plasma nitrate and nitrite levels were significantly increased in all three groups fed the nitrate-supplemented water. Conclusion: Low and moderate dose nitrate significantly improved endothelial function and atherosclerotic plaque composition in ApoE-/- mice fed a HFD.